DMAP‐Catalyzed Efficient Diastereo‐ and Regioselective Synthesis of Isoxazolone‐Based Bisspiroheterocyclic Oxindoles - Zhu, Rong‐Rong; Du, Da‐Ming (European journal of organic chemistry, 2024)
A strategic approach to incorporate CF3 group into oxindoles, pyrrolidines, and isoxazolones to construct spiro heterocyclic skeletons with quaternary carbon stereocenters was developed. Using a DMAP catalyst under mild conditions, the controllable synthesis of spiro oxindole‐pyrrolidine‐isoxazoline derivatives was achieved via concerted 1,3‐dipolar cycloaddition reactions of arylidene isoxazolones with N‐(2,2,2‐trifluoroethyl)isatin ketimines. This method exhibits robust regioselectivity and provides a series of isoxazolone‐based bispiro heterocycles in good to high yields (72 %–99 %) with excellent diastereoselectivity (in all cases >20 : 1 dr), offering new candidate compounds for drug screen. A DMAP‐catalyzed diastereoselective 1,3‐dipolar cycloaddition reaction of arylidene isoxazolones with N‐(2,2,2‐trifluoroethyl)isatin ketimines is reported, which provides an efficient access to spiro oxindole‐pyrrolidine‐isoxazolone derivatives bearing CF3 group and quaternary carbon stereocenters in good to high yields with excellent diastereoselectivity.